IMPLEMENTASI KEBIJAKAN PARIWISATA DI DESA KALIPUCANG KECAMATAN TUTUR KABUPATEN PASURUAN - Roudotul Jannah; Daimul Abror (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
Kalipucang Village as one of the tourist village areas has tremendous potential in tourism development. However, the socio-economic conditions of the community tend to be relatively simple, so it is necessary to carry out an in-depth analysis of the implementation of tourism policies in Kalipucang Village, Tutur District, Pasuruan Regency. The purpose of this research is to find out what form of Tourism Policy Implementation in Kalipucang Village is in line with the theory of George and Edward III. This study used a qualitative approach with data collection techniques in the form of observation, interviews with the village government, Pokdarwis and local communities and documentation. The results showed that the implementation of the tourism policy in Kalipucang village has been implemented well. The communication carried out by the Policy Actor (Village Government) with the community is quite good with the openness of the problems faced. Natural resources are so abundant that the people of Kalipucang Village are enthusiastic in developing the Tourism Village so that it is more famous and visited by many domestic and foreign tourists. The problems faced by the people of Kalipucang Village are the not yet optimal work in each field, especially the tourism sector due to limited capital, inadequate tourism supporting facilities and infrastructure, as well as tourist destinations that are not well organized. The supporting factors that exist include the variety of tourism potentials available, the support of local management and community leaders, cooperation between community members and a very strong kinship and mutual cooperation attitude.